Rutin inhibits the in vitro formation of advanced glycation products and protein oxidation more efficiently than quercetin - Dias, Danyelle Trevisan Macedo [UNESP]; Palermo, Karen Ramalho [UNESP]; Motta, Bruno Pereira [UNESP]; Kaga, Anderson Kiyoshi [UNESP]; Lima, Tayra Ferreira Oliveira [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Baviera, Amanda Martins [UNESP] (Editora Cubo, 2021)
Introduction: The exacerbated generation of advanced glycation end products (AGEs) triggers the onset of diabetic complications associated with hyperglycemia. The search for natural bioactive compounds that can inhibit AGE formation has gained immense interest. Quercetin and its glycoside derivative, rutin, are powerful antioxidants. They have been studied due to their potential to mitigate the disturbances observed in diabetes; however, studies comparing their antiglycation effects are limited. The aim of the present study was to compare the in vitro antiglycation potentials of quercetin and rutin. Methods: The in vitro model system of protein glycation was applied using bovine serum albumin (10 mg/mL) incubated with glucose (0.5 M) in the absence or presence of aminoguanidine (1 mM, prototype anti-AGE agent), metformin (1 mM), quercetin (100, 50, or 12.5 µM), or rutin (100, 50, or 12.5 µM). Before initiating incubations (day 0) and after 10, 20, and 30 days, aliquots were assayed for fluorescent AGEs. Markers of amino acid oxidation (dityrosine, N’-formylkynurenine, kynurenine), protein carbonyl groups (PCO), and protein crosslink formation were assessed after 30 days. Results: Both quercetin and rutin inhibited the formation of AGEs and decreased the PCO levels in a concentration-dependent manner, and moreover, the effect of rutin was more prominent than that of quercetin. Quercetin and rutin also decreased the formation of amino acid oxidation products and protein crosslinks; the best effects were observed in incubations with rutin. Conclusion: Rutin exhibited the most potent antiglycation and antioxidant activities, which may be attributed to the minor occurrence of interactions between albumin and rutin, making rutinnoside more available to exert its effects.
Keywords: diabetes mellitus; In vitro model systems; Protein crosslinking; Protein glycation; Quercetin; Rutin